The Effects of Lateral Shift Correction Squat on Muscle Activation and Dynamic Balance in Scoliosis (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to effects of the muscle activity of elector spinae and gluteus maximus and dynamic balance ability during lateral shift correction squat in scoliosis.Method/Statistical Analysis: The subjects of this study were 17 female and 11 male who has scoliosis were recruited. Surface electromyography data were collected from the both of electer spinae(T6 and L3) and gluteus maximus. Dynamic balance was collected from bio-resque device. A Paired t - test was performed to examine the effect of both of elector spinae(T6 and L3) and gluteus maximus muscle activity and dynamic balance during lateral shift correction squat.Findings: The results of this study show that the trunk lateral shift correction squat increased ratio of elector spinae(T6 and L3) and gluteus maximus compared with general squat. Also dynamic balance ability was increased during lateral shift correction squat compared with general squat.Improvements/Applications: This study suggests that lateral shift squat maybe useful in subject with scoliosis.